LITERASI BACA SISWA KELAS AWAL DI DESA HUTABAYU DENGAN MODEL CONTEXTUAL TEACHING AND LEARNING (CTL) BERBASIS ETNOBUDAYA - Yanti Arasi Sidabutar; Hasratuddin; Retno Dwi Suyanti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The aim of this research was to develop a Contextual Teaching and Learning (CTL) Model integrated with Batak ethnoculture and to test its effectiveness in improving the reading literacy of elementary school students. This study was necessary because of the students' low reading literacy levels and the lack of connection between teaching materials and the students' local and cultural context, which can hinder understanding. This development research used the Plomp model. The analysis phase included questionnaires and interviews to identify curriculum needs and relevant Batak ethnocultural richness. The CTL model based on Batak ethnoculture was designed as a learning package, including the syllabus, lesson plans (RPP), and teaching materials that featured folktales and Batak values. To test effectiveness, a quasi-experimental design was used. This involved an experimental group using the Batak ethnoculture-based CTL model and a control group using a conventional teaching model. Data was collected through reading literacy tests (comprehension, interpretation, and reflection) and student/teacher response questionnaires. The results showed that the developed Batak ethnoculture-based CTL Model met the criteria for validity, practicality, and effectiveness. The average scores on the reading literacy test for the experimental group were significantly (p<0.05) higher than those of the control group.